Une approche synoptique des théories de la décision, de la puissance et de la négociation - Barrea, Jean (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
Assuming that the synoptic reading of partial theories is of use in the building of cumulative theories, the author seeks to establish common points between theories of the decision-making process in foreign policy and theories of power and egotiation at the international level. This paper seeks as well to complement these latter two types of theory with the findings of decision theory. After having justified his undertaking by the relations existing between observed phenomena - that is, decision, power and negotiation - and by the absence of a theory taking these three phenomena into account, the' author sets out the plan of his reflection in function of the distinctions between the approaches and factors emphasized by the various decision theories. The text considers the defining elements of the most important contributions of the specialists on the question. To conclude, the author provides a synoptic table of the main observations of his analysis. This table, which in the author's opinion is able to account for specific situations that are not explicitly described therein, demonstrates that the paradigms of theories of power and negotiation may only be established by reference to the decision paradigm.